Design of Ku-band power divider using Substrate Integrated Waveguide technique - Tan Gan Siang; David Paul David Dass; Siti Zuraidah Ibrahim; Mohd Nazri A. Karim; Aliya A. Dewani (Institute of Advanced Engineering and Science, 2019)
A Ku-band Substrate Integrated Waveguide power divider is proposed. In this work, the SIW power divider is designed with T-junction configuration. The SIW technique enables the power divider to have low insertion loss, low cost and features uniplanar circuit. An additional of metallic via hole is added in the center of the junction to improve the return loss performance of the Tjunction SIW power divider. The simulated input return losses at port 1 are better than 27 dB, and features equal power division of about -3.1 dB ±0.4 dB at both output ports across frequency range of 13.5-18 GHz. The SIW power divider is fabricated, and the measurement results show acceptable performances. Since there are some losses contributed by the SMA connector of the fabricated SIW power divider prototype, an additional SIW transmission line is simulated and fabricated to analyze the connector loss.